Analisis Pengaruh Penggunaan Pestisida Nabati Terhadap Hama Dan Penyakit Tanaman - Laoli, Tri boi Selamat; Malo, Maximilianus (CV. SINAR HOWUHOWU, 2025)
Emergency vegetable pesticides as an environmentally friendly solution for controlling pests and diseases in plants. This research aims to analyze the effectiveness of botanical pesticides made from neem (Azadirachta indica) and soursop leaf (Annona muricata) leaf extracts on pest populations, disease attack levels and plant productivity. The research was carried out experimentally with four treatments: P1 (neem extract), P2 (soursop extract), P3 (combination of neem and soursop), and P4 (control). The research results showed that combination treatment (P3) gave the best results with a reduction in pest populations reaching 80% and the intensity of disease attacks reduced by 75%. In addition, the P3 treatment also succeeded in increasing crop yields by 57% compared to the control. Thus, botanical pesticides have proven effective in controlling pests and diseases, while increasing plant productivity. These findings demonstrate the potential of botanical pesticides as a sustainable alternative in modern agricultural systems. .